Adjunct ultrasonography for breast cancer screening in women at average risk: a systematic review. Issue 2 (10th June 2013) - Gartlehner, Gerald; Thaler, Kylie J; Chapman, Andrea; Kaminski, Angela; Berzaczy, Dominik; Van Noord, Megan G; Helbich, Thomas H
Abstract Background Screening with mammography has the ability to detect breast cancer at an early stage but misses some cancers. Supporters of adjunct ultrasonography to the screening regimen argue that it might be a safe and inexpensive approach to reduce the false‐negative rates of screening. Critics are concerned that adjunct ultrasonography will also increase the rate of false‐positive findings and can lead to unnecessary biopsies and treatments in women at average risk. Aims The purpose of this review was to systematically assess the comparative benefits and harms of mammography with adjunct breast ultrasonography and mammography only in breast cancer screening. Methods We searched multiple electronic databases and the Cochrane Breast Cancer Group's Specialised Register (from 1995 to February 2012). To detect ongoing or unpublished studies, we searched trial registries and multiple sources of grey literature. Two researchers independently reviewed all abstracts and full‐text articles against pre‐defined eligibility criteria. We dually rated the risk of bias of studies and the strength of evidence based on established guidance. Results We did not detect any controlled studies that provide evidence for (or against) the use of adjunct ultrasonography for screening in women at average risk for breast cancer. Extrapolations of results from women at elevated risk for breast cancer indicate that the false‐positive rates in women at average risk who were recalled because of positive ultrasonographies will exceed 98%. In women with dense or very dense breast tissue, the evidence regarding the use of adjunct ultrasonography is not conclusive. Conclusions No methodologically sound evidence is available justifying the routine use of ultrasonography as an adjunct screening tool in women at average risk for breast cancer. Implications for practice Clinicians should not use ultrasonography as a screening tool for breast cancer screening on a routine basis. The use should be limited to women with dense breasts for whom the accuracy of mammography is low, or for diagnostic purposes.